THE QUESTION OF WOMEN'S WILL IN "BUTTERFLY SEASON" (Academicia Globe: Inderscience Research, 2022)
The image of women is currently being studied as an important issue in all forms of art (cinema, theater, sculpture, painting, dance, fiction, art history, psychology, etc.). The main inspiration for great works was mostly women. The article also reveals various psychological layers in the study of the image of the narrator. It can be used in the process of analyzing a work of art.